Terapi Sufistik Metode Taubat dalam Pembentukan Kepribadian Sehat - Prayoga Restu Tito (Gunung Djati Conference Series, 2023)
In this modern era there have been many changes both in terms of technology, social, values, culture and many more. The thing that might be a problem for today's generation is personality. If you look at the current condition, humans tend to behave arbitrarily, even with the existence of regulations, they are ignored by them to commit violations everywhere, crimes are increasing, fear, anxiety, anxiety are increasingly attached to humans. This article discusses forming a healthy personality using a sufistic method, namely repentance, repentance is used as a method to improve the personality of modern society so that it returns to being a healthy person and free from mental disorders. This study uses qualitative research methods using library research that examines previous research. The results of the study show how great the influence of repentance is to make a person's personality healthy and avoid some deviant things.